МЕТОДОЛОГО-ПРАГМАТИЧЕСКАЯ ХАРАКТЕРИСТИКА ИГРЫ В СЛОВА В УЗБЕКСКИХ АНЕКДОТАХ (Scientific journal of the Fergana State University, 2023)
This article talks about the methodological-pragmatic features and uniqueness of Uzbek national anecdotes and puns. The history of the appearance of word games, including anecdotes, is reviewed. Also, the study of word games as a research object of world linguistics and the history of the appearance of anecdotes are reviewed. In European science and Uzbek linguistics, attention is paid to sources related to the study of the text of anecdotes. Examples related to the image of Effendi, the main character of anecdotes, are analyzed and conclusions are given.